Photovoltaic powered uninterruptible power supply using smart relay - Ismail, Daut, Prof. Dr.; Muhammad Irwanto; Surya, Hardi (Institute of Electrical and Electronics Engineers (IEEE), 2010)
Link to publisher's homepage at http://ieeexplore.ieee.org/